Assess Nurse Perceptions of physical assessment skills for detecting acute progression of heart failure - Nabil Ayidh Shaeel Althiyabi,; Abdulrahman Juaidan Alotaibi,; Muteb Falah Saud,; Mohammed mutlaq jalotaibi,; Naif Juaidan Alotaibi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Physical assessment skills are crucial for nurses across clinical settings to accurately identify acute changes in patients, particularly in cases of heart failure. Existing research suggests that clinical experience significantly impacts nurses' proficiency and reliance on specific assessment skills, underscoring the need to evaluate how nurses perceive these skills according to their experience level and exposure to acute heart failure cases. Methods: This survey-based study included nurses from various hospitals, categorized into three experience groups and further subdivided based on experience with acute heart failure. A self-administered questionnaire assessed the perceived necessity of 48 physical assessment skills using a five-point Likert scale. Data analysis included Pearson’s Chi-square, Mann–Whitney U, and Kruskal–Wallis tests to compare perceived skill needs across experience levels and experience with acute heart failure. Results: Among 1,113 eligible nurses, 347 completed the survey (response rate: 93.0%). Experienced nurses with more than five years reported a higher perceived need for skills such as “dyspnea,” “stridor,” and “cyanosis,” while nurses with less experience rated the necessity of skills like “jugular venous distension” and “heart murmur” higher. Significant differences were found in skill perceptions between nurses with and without acute heart failure experience, particularly for skills related to respiratory and cardiovascular assessment. Additionally, as clinical experience increased, the perceived importance of certain assessment skills adapted to align with real-world practice demands. Conclusion: This study highlights that clinical experience and exposure to acute heart failure influence nurses’ perceived needs for specific physical assessment skills. Understanding these perceptions can inform targeted educational strategies, helping novice nurses develop the essential assessment competencies required in acute care settings, ultimately enhancing patient outcomes in cases of heart failure and other acute conditions.